KETENTUAN AMBANG BATAS DEFISIT ANGGARAN PENDAPATAN DAN BELANJA NEGARA (APBN) 3% DITINJAU BERDASARKAN PRINSIP KEPASTIAN HUKUM DALAM KONDISI DARURAT TERTENTU - Fibran Ahmad Firdaus; Aris Yuni Pawestri (Jurnal Yuridis, 2026)
This research examines the normative tension between the 3% GDP budget deficit ceiling under Law Number 17 of 2003 on State Finance and the fiscal flexibility introduced by Law Number 2 of 2020 during the COVID-19 pandemic emergency. The central issue is whether this rigid deficit ceiling satisfies the principle of legal certainty when applied under specific emergency conditions. This study employs normative legal research with a statute approach and a conceptual approach, employing a prescriptive analytical method. The findings indicate that the 3% ceiling, as a fixed legal norm, potentially conflicts with legal certainty principles when emergency conditions demand greater fiscal flexibility. This research recommends explicit normative reformulation governing deficit exceptions within a state financial law framework that remains adaptive yet measurable and accountable.